Polysaccharides from Fresh Viscum album L. Berry Extract and Their Interaction with Viscum album Agglutinin I - Edlund, Ute; Hensel, Andreas; Fröse, Diethelm; Pfüller, Uwe; Scheffler, Armin (Arzneimittelforschung, 2000)
A special microfiltrated colloidal preparation from fresh Viscum album L. berries was investigated concerning the occurrence and structural features of polymeric carbohydrates. A crude polysaccharide fraction was isolated from lectin-, tannin- and protein-depleted microfiltrates. Further fractionation by exchange chromatography revealed a neutral fraction (average molecular weight 30 kDa) and three acidic fractions (average molecular weights 1300 kDa). Structural analysis of the respective polysaccharide fractions by quantitative and qualitative determination of the sugar composition and linkage analysis indicated that all acidic fractions contained an acidic arabinogalactan with a rhamnose-galactoronic acid backbone and highly branched arabinose-galactose side chains attached by the rhamnose residues to the backbone. The neutral fraction consisted of a neutral arabinogalactan beside minor amounts (about 10%) of a low substituted xyloglucan. Further studies on interaction between the 1340 kDa acidic rhamno-arabinogalactans II and III and mistletoe lectin Viscum album agglutinin I (VAA I) revealed binding capacities between these compounds, while the neutral polymers interacted significantly less with VAA I. Only partial binding of VAA I was observed by incubation of the lectin with polysaccharide II. Similar interactions of polysaccharide fraction III with VAA I was measured in a BIACRORE biosensore system. Using the hemagglutination test, increased agglutination of erythrocytes was observed when mistletoes lectin I and the respective polysaccharide fractions were present together in the assay. All these data indicate clearly strong interaction between VAA I and Viscum polysaccharides.
Keywords: Mistletoe extracts; Viscum album agglutinin I; Viscum album L., arabinogalactan, polysaccharides, rhamnogalacturonan, xyloglucan